1997
DOI: 10.1074/jbc.272.50.31719
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence Context Effect of a Cyclobutane Pyrimidine Dimer upon RNA Polymerase II Transcription

Abstract: We have studied the role of sequence context upon RNA polymerase II arrest by a cyclobutane pyrimidine dimer using an in vitro transcription system consisting of templates containing a specifically located cyclobutane pyrimidine dimer (CPD) and purified RNA polymerase II (RNAP II) and initiation factors. We selected a model sequence containing a well characterized site for RNAP II arrest in vitro, the human histone H3.3 gene arrest site. The 13-base pair core of the arrest sequence contains two runs of T in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…The undamaged control template and the one with a single CPD in the nontranscribed strand behaved in the same way (Fig. 5), confirming previous reports that a CPD in the nontranscribed strand does not affect the behavior of a transcribing RNAP II (10), unless it has an effect on the inherent structure of the DNA helix (16). In this case, when a thymine dimer was introduced into the nontranscribed strand of a naturally strong RNAP II transcription arrest site, it caused the arrest site to become weaker and only transiently arrested the polymerase.…”
Section: Fig 4 Quantitation Of Read-through and Truncated Transcripsupporting
confidence: 77%
See 2 more Smart Citations
“…The undamaged control template and the one with a single CPD in the nontranscribed strand behaved in the same way (Fig. 5), confirming previous reports that a CPD in the nontranscribed strand does not affect the behavior of a transcribing RNAP II (10), unless it has an effect on the inherent structure of the DNA helix (16). In this case, when a thymine dimer was introduced into the nontranscribed strand of a naturally strong RNAP II transcription arrest site, it caused the arrest site to become weaker and only transiently arrested the polymerase.…”
Section: Fig 4 Quantitation Of Read-through and Truncated Transcripsupporting
confidence: 77%
“…Its atomic structure has been solved at a 2.8 Å resolution (36). Lesions that have been shown to block an elongating RNAP II in vitro when present on the transcribed strand include cisplatin GG intrastrand and interstrand cross-link (37)(38)(39), N-acetoxyacetylaminofluorene (40), psoralen monoadducts and interstrand cross-links (41), benzo(a)pyrene (42), and CPDs (10,16,17,43).…”
Section: Fig 4 Quantitation Of Read-through and Truncated Transcripmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to understand the role of mammalian RNA polymerase II (RNAP II) in TCR, we have developed an in vitro transcription system with templates containing a site-specific lesion positioned downstream of the adenovirus major late promoter (AdMLP) and purified proteins and initiation factors. Using this in vitro transcription system, we have previously shown that a cyclobutane pyrimidine dimer in the transcribed strand in different sequence contexts is a strong block to RNAP II (9,10). The arrested polymerase is stable and competent to resume transcription.…”
Section: Transcription-coupled Repair (Tcr)mentioning
confidence: 99%
“…These DNA lesions alter DNA structure and pose a block to elongating RNA polymerase II complexes; so, UV light leads to a dose-dependent decrease in the synthesis of nascent mRNA (Fig. 1A) (69,101,106,136,138,149). The probability that the synthesis of a specific mRNA is blocked is a function of UV dose and the length of the gene (136).…”
Section: Introductionmentioning
confidence: 99%